School Efforts In Increasing The Quality Of Education Which Decreased Due To The PPDB Zonation System - Prihanarko, Arvenda; Santosa, Achadi Budi (Journal Of Educational Experts (JEE), 2023)
The purpose of enacting the Regulation of the Minister of Education and Culture No. 17 of 2017 concerning Acceptance of New Students (PPDB) with the zoning system, is for equal distribution of quality and access to Indonesian education. However, it turns out that equality of quality education has not been achieved so far, and is even suspected of reducing the quality and output of these schools. Students' learning motivation becomes low, confusion of teachers who teach students who are more intellectually heterogeneous.The school's efforts to improve the quality of education which has declined as a result of the zoning system policy are by seeking anticipation from the side of the school principal, teachers, students, infrastructure and the involvement of parents and the community.Schools are at the forefront in dealing with the problem of the declining quality of education. Schools must be able to innovate and anticipate and update as quickly as possible.